Szanse i ryzyko operacji giełdowych w warunkach wielkich kryzysów finansowych - Stasch, Anton (Przegląd Prawno-Ekonomiczny, 2009)
Streszczenie dostępne wyłącznie w języku angielskim: The next crash of USA stock market is expected no later than 2013. The real cause of the next crisis will be, similar as in the crisis of 2007-2009, the overvaluation of objects of speculation. Their value, corresponding to the value of global financial assets. grew in 2006 to 650 thousand bilion (650billions)U.S. . This value overestimates 13,5-fold the world annual Gross Domestic Product, of 48.3 billions US . In 1980 both values, GDP and value of assets were approximately equal to ten billions US . One of the main reasons for the bursting of speculation bubble in 2007 was vote buying of NINJA electors by politicians using the state full controlled financial institutions like banks: Fannie Mae and Freddie Mac.